Mechanism for the development of quality services according to the Islamic perspective / Masthurhah Ismail and Mohd Zahirwan Halim Zainal Abidin - Ismail, Masthurhah; Zainal Abidin, Mohd Zahirwan Halim (Universiti Teknologi MARA, Perak, 2011)
Service quality in an organization is crucial to ensure an objective outlined is reached. Various efforts have been made to improve the quality of an organization, particularly public organizations. This effort is required in Islam because it gives many benefits to all parties. This paper will delve into the mechanisms of development of quality from an Islamic perspective. The most important mechanism is to return to the application of the value of tawheed in the development of service quality as well as application of the other values recommended in Islam. This is because the journey of life and execution of all deeds in Islam are contained in a tawheed framework which has the ambitious goal of maintaining relations with people and to keep in touch with nature to ensure a good everlasting relationship with God.